Identification of an HLA-A*0201-Restricted T-Cell Epitope on the MPT51 Protein, a Major Secreted Protein Derived from Mycobacterium tuberculosis, by MPT51 Overlapping Peptide Screening - Aoshi, Taiki (American Society for Microbiology (ASM), 2008)
CD8(+) T cells play a pivotal role in protection against Mycobacterium tuberculosis infection. We identified a novel HLA-A*0201-restricted CD8(+) T-cell epitope on a dominant secreted antigen of M. tuberculosis, MPT51, in HLA-A*0201 transgenic HHD mice. HHD mice were immunized with plasmid DNA encoding MPT51 with gene gun bombardment, and gamma interferon (IFN-γ) production by the immune splenocytes was analyzed. In response to overlapping synthetic peptides covering the mature MPT51 sequence, the splenocytes were stimulated to produce IFN-γ by only one peptide, p51-70. Three-color flow cytometric analysis of intracellular IFN-γ and cell surface CD4 and CD8 staining revealed that the MPT51 p51-70 peptide contains an immunodominant CD8(+) T-cell epitope. Further analysis using computer algorithms permitted identification of a bona fide T-cell epitope, p53-62. A major histocompatibility complex class I stabilization assay using T2 cells confirmed that this epitope binds to HLA-A*0201. The T cells were capable of lysing MPT51 p53-62 peptide-pulsed T2 cells. In addition, MPT51 p53-62-specific memory CD8(+) T cells were found in tuberculin skin test-positive HLA-A*0201(+) healthy individuals. Use of this HLA-A*0201-restricted CD8(+) T-cell epitope for analysis of the role of MPT51-specific T cells in M. tuberculosis infection and for design of vaccines against tuberculosis is feasible.